Análisis de riqueza y diversidad de un bosque de colina baja, Loreto – Perú. 2021 - Cárdenas Meléndez, Dana Madeleine (2021)
These aim of this study was to determine the richness and diversity of species in a low-hill forest of the forestry concession for timber purposes of the company Aserradero Forestal Becerra EIRL, Mazan, Loreto. 46 sampling units of 10 m x 500 m were evaluated. A total of 2418 trees are reported, grouped into 90 species, 76 genera and 28 botanical families. Virola sp. with 559 trees (23,12%) is the species with the highest number of trees, followed by Eschweilera albiflora with 559 trees (11,50%). The curve obtained from the diametric distribution of the number of trees looks like an “inverted J”, which indicates a higher number of individuals in the lowest classes and, as the diameter increases, the number of individuals gradually decreases. The most important species are Virola sp. (48,76%), Eschweilera albiflora (25,34%), Licania triandra (15,07%), Perebea guianensis (14,12%), Ocotea longifolia (13,94%), Tachigali bracteosum (10,69%), Pouteria hispida (10,40%), Ormosia sp. (9,07%) and Ceiba samauma (8.97%). Average diversity is reported according to the diversity indices of Shannon-Viener, Margalef and Simpson. A p = 0,9996 in the ANVA, at a significance level of α = 0.05, indicates no significant differences in species diversity among the sampling units.